Application of magnetically treated water during initial growth of bell pepper seedlings - Zolin Lorenzoni,Marcelo (Universidad de Tarapacá. Facultad de Ciencias Agronómicas, 2021)
ABSTRACT The cultivation of bell peppers, before transplanting, starts in nurseries to obtain uniform and vigorous seedlings. This study aimed to evaluate the effect of applying magnetically treated water on germination and the initial growth of bell pepper seedlings. Two experiments were conducted from August to October 2018 in a protected environment at the Irrigation Tecnic Center (CTI/ UEM) - Maringá, Paraná: the first in 50-cell polyethylene trays and the second in plastic containers (180 ml). Both experiments were filled with a commercial substrate (Su) and commercial substrate + soil mix (SS). The substrate was irrigated daily for the germination test, according to the corresponding treatment, and germination was quantified in the first 15 days after emergence to obtain the germination percentage and the final emerged percentage. Seedling growth was evaluated based on the following criteria at 43 days after sowing: height, stem diameter, total fresh mass, total dry mass, chlorophyll A and B, and carotenoids. The results showed that the application of magnetically treated water to seeds promoted germination one day prior to those irrigated without treatment when cultivated with SS. There was significant interaction for the chlorophyll A, with a 42% increase in SS cultivation with the application of magnetically treated water compared to the application of non-treated water. For the other variables, there were significant responses only in SS cultivation. Application of magnetically treated water caused higher gravimetric humidity in three out of ten evaluations, showing a significant reduction of evaporation in Su and SS cultivation.